An experimental study of the effect of water content on combustion of coal tar/water emulsion droplets - Deng, Shengxiang; Zhou, Jiemin (Energy (Oxford), 2011)
Isolated high asphaltene droplets of coal tar/water emulsion were studied to investigate the non-steady behavior of the burning droplets. Data on size and temperature histories were obtained. Coke residues were analyzed by scanning electron microscope. Lower and upper limits for ignition time delay were established. The error, defined as the time lag between these two limits, was less than 8 ms. Ignition time delays of emulsions were longer than for ordinary coal tar (CT) droplets of the same size but the peak temperature of emulsions occurred much earlier. A steeper temperature rise observed in the emulsions during portions of their combustion history is evidence not only of soot reduction but also the extent of burnout of the cenospheres. The latter is an important aspect in the reduction of pollutant emissions. The emulsion droplets indicated swelling of considerable magnitude compared with that of CT. Coke particles formed from emulsions were more porous, with thinner and fragile shells. The CT residues were harder and more resistant to burning. Excess burnout time or the ratio of burnout time of the emulsions depended on the water concentration, indicating that longer oxidation time was required for coke particles from coal tar than from emulsions. ► The droplet was subject to disruptive behavior in the pre-ignition and visible flame period. ► The coke particle from the emulsion presented more fragile and thinner shells than that of the CT. ► The steeper temperature rise was observed in the emulsions. ► Swelling of the emulsions occurred earlier than for CT-A droplet. ► The morphology of the CT carbonaceous residue was denser than that of the emulsion carbonaceous residue.